The Effect of Endurance Training on Blood Lactate Concentration and Anaerobic Threshold in Bangladeshi Female Handball Athletes - Sharmin Akter Shanta; Ajita (Physical Education Theory and Methodology)
Background. Endurance training has an essential role in improving the aerobic capacity and postponing the onset of exhaustion that can be beneficial to enhancing the performance. Handball involves both aerobic and anaerobic energy systems in the human body. Therefore, it becomes crucial to comprehend how training influences physiological variables such as anaerobic threshold and blood lactate concentration.